2022
DOI: 10.1002/btm2.10441
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic cell membrane‐coated poly(lactic‐co‐glycolic acid) nanoparticles for biomedical applications

Abstract: Poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) are commonly used for drug delivery because of their favored biocompatibility and suitability for sustained and controlled drug release. To prolong NP circulation time, enable target-specific drug delivery and overcome physiological barriers, NPs camouflaged in cell membranes have been developed and evaluated to improve drug delivery. Here, we discuss recent advances in cell membrane-coated PLGA NPs, their preparation methods, and their application to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 297 publications
0
27
0
Order By: Relevance
“…These functionalized nanoformulations specifically target intercellular adhesion molecule-1 (ICAM-1) via γ3 peptide on their surface and ultimately eradicate the K. pneumoniae with the help of loaded ciprofloxacin. The RBC membrane coating over the nanoparticles offers the properties of prolonged circulation time and immune escape ( 45 , 46 ). Further investigations indicated that γ3-RBCNPs have good antibacterial efficacy, good bio-safety, and long half-life in mice mode ( 51 ).…”
Section: Major Food Animal Pathogens Treated Through Cell Membrane-co...mentioning
confidence: 99%
See 1 more Smart Citation
“…These functionalized nanoformulations specifically target intercellular adhesion molecule-1 (ICAM-1) via γ3 peptide on their surface and ultimately eradicate the K. pneumoniae with the help of loaded ciprofloxacin. The RBC membrane coating over the nanoparticles offers the properties of prolonged circulation time and immune escape ( 45 , 46 ). Further investigations indicated that γ3-RBCNPs have good antibacterial efficacy, good bio-safety, and long half-life in mice mode ( 51 ).…”
Section: Major Food Animal Pathogens Treated Through Cell Membrane-co...mentioning
confidence: 99%
“…The cell membrane coatings over nanoparticles give the appearance of surfaces of naturally occurring cells in the body, that when correctly selected and prepared do not have any risk of immune system activation and attack ( 38 ). The biomimetic therapeutic design demonstrates several therapeutic benefits like capability of biointerfacing ( 42 , 43 ), biocompatibility ( 44 ), prolonged duration of circulation ( 45 ), immune evasion ( 46 ), and protection of the entrapped drug from active targeting and degradation ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“… 4 7 Nanoparticles (NPs) have the capability of selectively accumulating in the tumor site through passive targeting, also known as the enhanced permeability and retention effect, which prolongs their circulation time. 8 , 9 Our previous reports illustrated some of the beneficial properties of NPs favoring radiosensitizer agents in cancer treatment. 10 12 NPs containing high atomic number (Z) elements, also known as heavy elements, such as gold (Au), gadolinium (Gd), and bismuth (Bi), have been shown as potential radiosensitizer agents due to their high X-ray photon capture cross section and Compton scattering effect.…”
Section: Introductionmentioning
confidence: 96%
“…There is a widespread consensus that radiosensitization efforts should prioritize the integration of nanotechnology and radiation. In recent years, nanotechnology has been frequently used as a potential cancer detection and treatment technique in theranostics applications. Nanoparticles (NPs) have the capability of selectively accumulating in the tumor site through passive targeting, also known as the enhanced permeability and retention effect, which prolongs their circulation time. , Our previous reports illustrated some of the beneficial properties of NPs favoring radiosensitizer agents in cancer treatment. NPs containing high atomic number (Z) elements, also known as heavy elements, such as gold (Au), gadolinium (Gd), and bismuth (Bi), have been shown as potential radiosensitizer agents due to their high X-ray photon capture cross section and Compton scattering effect. , High Z-elements can release photoelectrons and Auger electrons under the X-ray irradiation which damage cancer cells through dose enhancement effect during radiation therapy . Due to their excellent absorption and ability to generate secondary electrons, AuNPs can boost X-ray dosage deposited in the tumor region and are considered potential radiation therapy sensitizers in cancer therapy .…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, inflammation is a controlled process in which numerous cells and soluble factors interact with each other in an attempt to limit or prevent the spread of injury [3,4]. However, when the inflammatory process becomes uncontrolled, it would contribute to the development of many complex disorders like autoimmune diseases and chronic inflammatory diseases [1,5]. Many factors may become involved in the inflammatory process, among which is angiotensin II (Ang II).…”
Section: Introductionmentioning
confidence: 99%